FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK - Rustiyaningsih, Sri (Widya Warta, 2011)
Taxes are a source of state revenues used for government spendings. The government has tried to raise taxation revenues. Tax revenues can be increased if taxpayers have a compliance in meeting tax obligations. There are several factors that affect taxpayers’ compliance to meet tax obligations, such as the understanding on the self-assessment system, educational level, income level, service quality, and the perception of taxpayers toward the tax penalties. The efforts of government to increase taxpayers’ compliance include publishing and sending letters of reprimand, making appeals, handing in tax bills, stimulating community awareness of the tax, improving the quality of tax-service offices, helping taxpayers to meet obligations of tax administration, socializing taxation so as to give taxpayers comprehensive understanding due to their rights and obligations, simplifying the available tax systems, and carrying out auditings in order to judge the owed taxes.